2011
DOI: 10.1124/mol.111.072470
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-Dependent Actin Reorganization: Bringing the Right Players Together at the Leading Edge

Abstract: First identified as mediators of G-protein-coupled receptor desensitization and internalization and later as signaling platforms, ␤-arrestins play a requisite role in chemotaxis and reorganization of the actin cytoskeleton, downstream of multiple receptors. However, the precise molecular mechanisms underlying their involvement have remained elusive. Initial interest in ␤-arrestins as facilitators of cell migration and actin reorganization stemmed from the known interplay between receptor endocytosis and actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…As shown, bPTH was more effective than serum or hPTH at stimulating wild-type osteoblast migration. Consistent with the reported roles of arrestin scaffolds in GPCR-regulated actin cytoskeletal dynamics and chemotaxis (44,60,62), bPTH had no effect in ␤-arrestin2-null osteoblasts. Supportive of our functional genomic analysis of calvarial bone, these data suggest that ␤-arrestin2 plays a regulatory role in the control of preosteoblast proliferation and mediates the effects of conventional and arrestin pathway-selective PTH 1 R agonists on osteoblast survival and migration.…”
Section: ␤-Arrestin2 Regulates the Proliferation Survival And Migrasupporting
confidence: 88%
“…As shown, bPTH was more effective than serum or hPTH at stimulating wild-type osteoblast migration. Consistent with the reported roles of arrestin scaffolds in GPCR-regulated actin cytoskeletal dynamics and chemotaxis (44,60,62), bPTH had no effect in ␤-arrestin2-null osteoblasts. Supportive of our functional genomic analysis of calvarial bone, these data suggest that ␤-arrestin2 plays a regulatory role in the control of preosteoblast proliferation and mediates the effects of conventional and arrestin pathway-selective PTH 1 R agonists on osteoblast survival and migration.…”
Section: ␤-Arrestin2 Regulates the Proliferation Survival And Migrasupporting
confidence: 88%
“…In the process of internalization, clathrin is first recruited to assemble at the cell membrane, then forms clathrincoated pits to move the target proteins into the cells, and finally the pits lose their coats and deliver the endocytic vesicles to the early endosome (Smythe and Ayscough, 2006). Previous studies have revealed that β-arrestin1 and β-arrestin2 have a domain that directly interacts with clathrin, and thereby triggering the endocytic events via clathrin-coated pits (Gavard and Gutkind, 2006;Min and Defea, 2011). It is noteworthy that tight junction proteins, including claudin-1, claudin-4, occludin and ZO-1, are internalized by clathrin in T84 epithelial cells (Ivanov et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that β-arrestin2 has a domain that directly interacts with clathrin, thereby evoking internalization or endocytosis of target membrane proteins through the clathrindependent pathway (Gavard and Gutkind, 2006;Min and Defea, 2011). Therefore, we examined whether an interaction between claudin-4 and clathrin was induced by carbachol.…”
Section: Claudin-4 Is Internalized In a Clathrin-dependent Waymentioning
confidence: 99%
“…Thus, b-arrestins can both terminate and initiate cell signaling pathways. Importantly, barr2-dependent signaling has been shown to promote cellular chemotaxis and antiapoptosis, implicating barr2 in inflammation/metastasis (9) and propelling the investigation of its role in the study of cancer (10)(11)(12)(13)(14), atherosclerosis (15), and inflammatory disorders, including asthma.…”
Section: Clinical Relevancementioning
confidence: 99%